Write the prime factorization of each monomial given below. Do not use exponents.
1) 25n2
2) 18xy
3) 12y
4) 21y2
5) 81a
6) 92q
7) 36x3
8) 24h
9) 48x2
10) x2y3
11) 20b3c2
12) 82ab
13) 91yz2
14) 66y
15) -18g4h
16) 15n/30n3
17) 8x2/12x4
18) 24x2 y/32xy3
19) (x + 1)3/(x + 1)5
20) (2n - 3)/(3 - 2n)
21) 24x3 (4 - x)/18 x (4 - x)
22) (3x - 2)6/(3x - 2)4
23) (a2 + 6a) / (ac + 6c)
24) 12x3 (5 - 2x) / 18x (2x - 5)
25) 15y(y + 1) / 45y2(y + 1)
26) (6 - 8x)/(4x2 - 3x)
27) (ax - ay + bx - by) / (ax - ay - bx + by)
28) (xy + 3x - 2y - 6)/(y2 + y - 6)
1. Answer :
25n2 = 5 ⋅ 5 ⋅ n ⋅ n
We may write the repeating factors using exponential form.
= 52 ⋅ n2
2. Answer :
18xy = 2 ⋅ 3 ⋅ 3 ⋅ x ⋅ y
= 2 ⋅ 32 ⋅ xy
3. Answer :
12y = 2 ⋅ 2 ⋅ 3 ⋅ y
= 22 ⋅ 3 ⋅ y
4. Answer :
21y2 = 3 ⋅ 7 ⋅ y ⋅ y
= 3 ⋅ 7 ⋅ y2
5. Answer :
81a = 3 ⋅ 3 ⋅ 3 ⋅ 3 ⋅ a
6. Answer :
92q = 2 ⋅ 2 ⋅ 23 ⋅ q
7. Answer :
36x3 = 2 ⋅ 2 ⋅ 3 ⋅ 3 ⋅ x ⋅ x ⋅ x
8. Answer :
24h = 2 ⋅ 2 ⋅ 2 ⋅ 3 ⋅ h
9. Answer :
48x2 = 2 ⋅ 2 ⋅ 2 ⋅ 2 ⋅ 3 ⋅ x ⋅ x
10. Answer :
x2y3 = x ⋅ x ⋅ y ⋅ y ⋅ y
11. Answer :
20b3c2 = 2 ⋅ 2 ⋅ 5 ⋅ b ⋅ b ⋅ b ⋅ c ⋅ c
12. Answer :
82ab = 2 ⋅ 41 ⋅ a ⋅ b
13. Answer :
91yz2 = 7 ⋅ 13 ⋅ y ⋅ z ⋅ z
14. Answer :
66y = 2 ⋅ 3 ⋅ 11 ⋅ y
15. Answer :
-18g4h = -1 ⋅ 2 ⋅ 3 ⋅ 3 ⋅ g ⋅ g ⋅ g ⋅ g ⋅ h
16. Answer :
= 15n/30n3
Both numerator and denominator are multiples of 15 and n.
= 15n / 15n(2n2)
= 1/2n2
17. Answer :
= 8x2/12x4
Both numerator and denominator are multiples of 4 and x2.
= 4x2(2)/4x2 (3x2)
= 2/3x2
18. Answer :
= 24x2 y/32xy3
Both numerator and denominator are multiples of 8, x and y.
= 8xy(3x) / 8xy(4y2)
= 3x/4y2
19. Answer :
= (x + 1)3/(x + 1)5
In both numerator and denominator, we have (x + 1)3 in common.
= = (x + 1)3/(x + 1)3 . (x + 1)2
By cancelling the common factors, we get
= 1/(x + 1)2
20. Answer :
= (2n - 3)/(3 - 2n)
Factoring - sign from the numerator or denominator, we get
= -(3 - 2n) / (3 - 2n)
By cancelling the common factor, we get
= -1
21. Answer :
= 24x3 (4 - x)/18 x (4 - x)
By cancelling the common factor (4 - x), we get
= 24x3 /18 x
Now 24 and 18 both are multiples of 6x.
= 6x(4x2) /6x(3)
= 4x2 / 3
22. Answer :
= (3x - 2)6/(3x - 2)4
= (3x - 2)4 (3x - 2)2/(3x - 2)4
Cancelling common factors, we get
= (3x - 2)2
23. Answer :
= (a2 + 6a) / (ac + 6c)
Factoring a from the numerator
= a(a + 6) / (ac + 6c)
Factoring c from the denominator
= a(a + 6) / c(a + 6)
Cancelling the common factors, we get
= a/c
24. Answer :
= 12x3 (5 - 2x) / 18x (2x - 5)
Factoring - sign from the numerator or denominator, we get
= -12x3 (2x - 5) / 18x (2x - 5)
= -12x3 / 18x
Both 12 and 18 are multiples of 6. Expressing this as factor of 6x, we get
= -6x(2x2) / 6x(3)
= -2x2 / 3
25. Answer :
= 15y(y + 1) / 45y2(y + 1)
Cancelling common factors, we get
= 15y / 45y2
Here 15 and 45 are multiples of 15.
= 15y/15y(3y)
= 1/3y
26. Answer :
= (6 - 8x)/(4x2 - 3x)
Factoring 2 form the numerator
= 2(3 - 4x)/(4x2 - 3x)
Factoring x from the denominator, we get
= 2 (3 - 4x)/x(4x - 3)
Factoring negative sign from the numerator, we get
= -2(4x - 3)/x(4x - 3)
= -2/x
27. Answer :
= (ax - ay + bx - by) / (ax - ay - bx + by)
= [a(x - y) + b(x - y)] / [a(x - y) - b(x - y)]
= (a + b)(x - y) / (a - b)(x - y)
Cancelling the common factors, we get
= (a + b)/(a - b)
28. Answer :
= (xy + 3x - 2y - 6)/(y2 + y - 6)
= [x(y + 3) - 2(y + 3)]/(y2 + 3y - 2y - 6)
= [x(y + 3) - 2(y + 3)]/[y(y + 3) - 2(y + 3)]
= [(x - 2)(y + 3)]/[(y - 2)(y + 3)]
= (x - 2) / (y - 2)
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Feb 04, 25 08:16 AM
Feb 04, 25 08:15 AM
Feb 04, 25 08:11 AM